Beginning iOS social games - Richter, Kyle (Apress Imprint: Apress, 2013)
It's certainly fun to build games that run on your iPhone and iPad. But, wouldn't it be more fun to create games that allow you to play with other gamers in your social network? There's a whole lot more things you can do. Most of the top best selling games around the world, like World of Warcraft, let you play with others online and share your experiences with your friends. Beginning iOS Social Games is your concise introduction to iOS social and other networked gaming app development using iOS Game Center, Game Kit, Store Kit, AirPlay, iOS 7 Game Controllers, iTunes App Store and integrating with social networks/media like Facebook and Twitter. Author Kyle Richter of Empirical Development is an expert game developer who guides you through the social game app development process step by step. This book may allow you to turn your already existing, created game into a well polished networkable and/or social media capable game app.